Sister mother warrior : a novel - Riley, Vanessa (William Morrow, an imprint of HarperCollins Publishers, 2022)
"Queen of diverse historicals Vanessa Riley brings readers a vivid, sweeping novel of the Haitian Revolution based on the true-life stories of two extraordinary women: the first Empress of Haiti, Marie-Claire Bonheur, and Gran Toya, a West African-born warrior who helped lead the rebellion that drove out the French and freed the enslaved people of Haiti"--